Deconstruction And Simulacra: A Postmodern Critique Of Management Science - Muhammad Ilham Alimuddin; Muhammad Yunus Amar (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2026)
This study analyzes management science and organizational practice through the lens of postmodernism, employing Derrida's deconstruction and Baudrillard's theory of simulacra to unpack the discursive structures and representational functions within contemporary management. Situated within the framework of Critical Management Studies (CMS), this research addresses the risk of stagnation and